2010
DOI: 10.1111/j.1365-2133.2010.09813.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated resolution of laser-induced bruising with topical 20% arnica: a rater-blinded randomized controlled trial

Abstract: Topical 20% arnica ointment may be able to reduce bruising more effectively than placebo and more effectively than low-concentration vitamin K formulations, such as 1% vitamin K with 0·3% retinol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…34,35 Analysis and Recommendation Three RCTs demonstrated positive outcomes of arnica for prevention of postprocedure ecchymosis and edema. Albeit these studies used small sample population and experimented with different treatment regimen of arnica (potency and duration), arnica demonstrated reduction of postprocedure ecchymosis and edema.…”
Section: A R N I C a A N D B R O M E L A I N F O R B R U I S I N G D mentioning
confidence: 98%
“…34,35 Analysis and Recommendation Three RCTs demonstrated positive outcomes of arnica for prevention of postprocedure ecchymosis and edema. Albeit these studies used small sample population and experimented with different treatment regimen of arnica (potency and duration), arnica demonstrated reduction of postprocedure ecchymosis and edema.…”
Section: A R N I C a A N D B R O M E L A I N F O R B R U I S I N G D mentioning
confidence: 98%
“…A double blind randomized placebo-controlled trial showed some improvement in severity of purpura, but not overall duration with the use of topical vitamin K cream [68]. Some efficacy in accelerating resolution of laser induced bruising has been observed with 5 % topical vitamin K ointment and Arnica 20 % ointment [69]. Counterintuitively, the PDL may be used at a nonbruising setting to help speed resolution.…”
Section: Lasersmentioning
confidence: 99%
“…Postprocedure bruising can be further minimized by having patients discontinue oral herbals and other medications (e.g., aspirin not prescribed by a doctor, vitamin E, and gingko) that may predispose. Some topical medications, such as vitamin K and arnica (4,5), may also be of limited utility in preventing or treating bruising. Paradoxically, use of the pulsed‐dye laser at nonbruising settings (for Candela Vbeam [Candela/Syneron, Wayland, MA, USA], 7.5 J, 6 ms, 10 mm with normal dynamic cooling device) can speed the fading of bruising that has already occurred (6).…”
Section: Minor Short‐term Complicationsmentioning
confidence: 99%